How Fear of COVID-19 Affects Service Experience and Recommendation Intention in Theme Parks: An Approach of Integrating Protection Motivation Theory and Experience Economy Theory - Pan, Yu; Xu, Jing (Bill); Luo, Jian Ming; Law, Rob (Frontiers in Psychology, 2022)
The unprecedented public panic caused by COVID-19 will affect the recovery of tourism, especially the theme parks, which are generally crowded due to high visitor volume. The purpose of this study is to discuss the effect of the COVID-19 on the theme park industry. This study aims to predict recommendation intentions of theme park visitors by exploring the complicated mechanism derived from the fear of COVID-19. This study uses a quantitative research method, and SPSS 20.0 and AMOS 22.0 were used for data analysis. An online survey was conducted with 420 Chinese respondents who visited Shanghai Disneyland after its reopening. The study explored the relationship between Fear of COVID-19, perceived risk, participation, service experience and revisit intention. Results indicated the perceived risk of theme park visitors will not directly ruin their recommendation intention. Visitors’ fear of COVID-19 enhanced their perceived risk, reduced their desire for active participation and impaired their service experience, which consequently affected their recommendation intention. We provide theoretical and managerial implications.